Habitat use of an endangered cyprinodontid fish in a saline wetland of the Iberian Peninsula (SW Mediterranean Sea) - VERDIELL-CUBEDO, D.; RUIZ-NAVARRO, A.; TORRALVA, M.; MORENO-VALCÁRCEL, R.; OLIVA-PATERNA, F.J. (Mediterranean Marine Science, 2013)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Aphanius iberus is an endemic fish restricted to a few populations along the Spanish Mediterranean coastline and included in international red lists. Information on its ecological requirements is needed to implement effective recovery and conservation measures. This two-year study aimed to analyse the effect of habitat changes, mainly in water salinity and refuge availability, on the life-history traits and microhabitat use of an A. iberus population inhabiting a littoral wetland managed for salt exploitation. The species was more abundant at the intake pond, which was characterised by lower water conductivity values and higher cover of the submerged macrophyte Ruppia cirrhosa. The pond with the highest values of water conductivity showed no presence of newborn individuals (< 10 mm), which probably indicates the reproduction failure of A. iberus or high mortality rates for younger individuals. Overall, the species’ selection of microhabitats was related to refuge presence (submerged vegetation and pond dykes). Juvenile individuals showed a strong dependence on sheltered microhabitats through the studied ponds, with R. cirrhosa meadows as important refuge areas for this age group. Results highlighted the importance of developing traditional maintenance and management measures for the conservation of such endangered fish species.